1998
DOI: 10.1093/jjco/28.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Cancer Metastasis and Lymphogenous Spread: Viewpoint of Animal Models of Lymphatic Obstruction

Abstract: Primary gastrointestinal cancer frequently spreads to the mesentery, omentum and other parts of the peritoneum and these deposits are generally considered to be induced by intraperitoneal seeding from the primary lesion. In this work, we examined the spread of gastrointestinal cancer from the viewpoint of lymphogenous metastasis using a rat model of mesenteric lymph vessel obstruction. With these models, we carried out mesenteric lymphangiography on the fourth and sixth postoperative days (five animals each) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 5 publications
2
14
0
1
Order By: Relevance
“…In our study we confirmed the formation of lymphatico-venous com- munication using mesenteric lymphatic obstruction in rats and reported the possibility that liver metastasis occurs by a lymphatic route [16]. Lymphangiography at early phase of rats with experimentally induced mesenteric lymphatic obstruction revealed distended mesenteric lymph vessels on the distal side of the obstruction and associated lymph retention and reflux [10]. From this, we considered that tumor cell obstruction in lymph vessels lead to the establishment of peritoneal metastasis.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our study we confirmed the formation of lymphatico-venous com- munication using mesenteric lymphatic obstruction in rats and reported the possibility that liver metastasis occurs by a lymphatic route [16]. Lymphangiography at early phase of rats with experimentally induced mesenteric lymphatic obstruction revealed distended mesenteric lymph vessels on the distal side of the obstruction and associated lymph retention and reflux [10]. From this, we considered that tumor cell obstruction in lymph vessels lead to the establishment of peritoneal metastasis.…”
Section: Discussionsupporting
confidence: 77%
“…It has been re-ported that lymphatic involvement is closely linked with peritoneal metastasis [8][9]. We have previously reported that in models of mesenteric lymph vessel obstruction in rats, we observed lymphatico-venous communication, retention and reflux of lymph within the mesentery [10]. This suggested that cancer cells metastasize to the liver or peritoneum by a lymphatic route.…”
Section: Introductionmentioning
confidence: 69%
“…It has been reported that lymphatic involvement is closely linked with liver metastasis [7,8]. We have previously reported that, in models of mesenteric lymph vessel obstruction in rats, we observed lymphaticovenous communication [9]. This suggested that cancer cells metastasized to the liver by a lymphatic route.…”
Section: Introductionsupporting
confidence: 51%
“…He referred to the possibility of liver metastasis occurring by a lymphatic route. In our previous study, we confirmed the formation of lymphaticovenous communication, using mesenteric lymphatic obstruction in rats, and reported the possibility that liver metastasis occurred by a lymphatic route [9]. From these findings, we considered that tumor cell obstruction in lymph vessels led to the establishment of liver metastasis, and, therefore, we studied extranodal invasion in resected specimens.…”
Section: Discussionmentioning
confidence: 62%
“…By using a rat model of mesenteric lymph vessel obstruction we previously demonstrated the occurrence of liver and peritoneal metastasis of digestive organ cancer caused by lymph retention [6][7][8]. In the present study we have focused on extranodal cancer invasion as a phenomenon of lymph retention due to the presence of cancer cells in the lymph system and demonstrated a strong relationship between extranodal invasion positive gastric cancers and peritoneal metastases9).…”
Section: Introductionmentioning
confidence: 60%